A4U - an approach to evaluation considering accessibility and usability guidelines - Amaral, Leandro Agostini do; Fortes, Renata Pontin de Mattos; Bittar, Thiago Jabur (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2018: Proceedings of the 24th Brazilian Symposium on Multimedia and the Web, 2018)
The Web presents an extensive information content available to diverse people, with different abilities and needs. For this reason, the evaluation for the universal accessibility and the usability are difficult tasks, even though having automatic tools to support them. In this context, it is also observed that the relationship between usability attributes and accessibility is too little explicitly considered, consisting of a research issue to be investigated. To support the integrated evaluation of accessibility and usability criteria, it was developed an environment for analyzing results of accessibility and usability assessments, thus allowing human evaluation, and the inclusion of evaluation results generated by semi-automatic tools, leading the evaluator to produce improvements on both fronts. We performed a case study, in which we observed the difficulties of inexperienced developers related to the description of the guidelines documented by the W3C and the U.S. Department of Health and Human Services (HHS). The cost for ensuring the objective criteria was the number of criteria to be checked, which tends to be high, leading to excessive time to review the application, but the experience in considering the concepts related to accessibility and usability, in the same environment, was positive.